Effect of a food supplement based on natural supplies and bioactive components of seven roots on sexual behavior in rats - Zamudio Malpartida, Karin (2020)
The present study aimed to determine the effect of a food supplement based on natural inputs and bioactive components of plant species on sexual behavior. It is an experimental, prospective and longitudinal investigation. For the test, 150 albino rats were used: 75 females and 75 males of the Holtzmann breed of 12 weeks of age, with an average weight of 200 to 250 g. (males) and 150 - 200 g. (females). Two products were evaluated: One that contained the extract of the roots of seven plant species at doses of 200 and 400mg / kg and Two that contained the product one plus chestnut flour and Sacha inchi at a dose of 830mg / kg. The trial was carried out for 10 weeks and the evaluations were carried out at the eighth, ninth and tenth weeks (days 1, 7 and 14 respectively). Likewise, the evaluation of the biochemical, hematological, testosterone and prostate-specific antigen (PSA) parameters was carried out. Products One at a dose of 400mg / kg and Two at a dose of 830mg / kg showed a significant effect on sexual behavior compared with the control and standard groups (sildenafil 5mg / kg). There were no changes at the biochemical or hematological level. It is concluded that the tested products had an effect on sexual behavior by increasing libido in male rats, without side effects on biochemical and hematological parameters.